An Integer Programming Model for Solving Integrated Hospital Capacity Management problem - et al., M. Irfan Fahmi (International Journal of Advanced Science and Technology, 2019)
Due to the increasing number of population, it is undoubtedly that the needs to get health services is rapidly growing. This situation also occur in Medan city, located in North Sumatera Province, Indonesia. For inpatient hospital care, it is necessary to consider capacity management systems which requires information on beds and nursing staff capacity. This paper presents a capacity model that gives insight into required nursing staff capacity and opportunities to improve capacity utilization on a ward level. A capacity model is developed to calculate required nursing staff capacity. A mixed integer nonlinear optimization is formulated to describe the problem. The model is implemented to a hospital in Medan city. The result is given in the paper.